Determinan Agresivitas Pajak pada Perusahaan Properti Dan Real Estate di Bursa Efek Indonesia - Alfia Nurul Fadhilah Putri; Cahyani Nuswandari (Universitas Batanghari Jambi, 2023)
Tax aggressiveness is an act of manipulating taxable income by companies through tax planning, both legally, namely tax advoidance, and illegally, namely tax evasion. The company's goal of carrying out tax aggressiveness is to minimize the tax burden by making it legal, illegal or both. This study aims to examine the influence of fixed asset intensity, inventory intensity, leverage, liquidity and company size on tax aggressiveness in property and real estate sector companies listed on the Indonesia Stock Exchange in 2017-2021. Sampling in this study using purposive sampling method. Data analysis in this study used multiple linear regression analysis. The results showed that preparation intensity had a positive and significant effect on tax aggressiveness, while leverage had a significant negative effect on tax aggressiveness. As long as the intensity of fixed assets, liquidity and company size have no effect on tax aggressiveness.